2011
DOI: 10.1246/cl.2012.107
|View full text |Cite
|
Sign up to set email alerts
|

Photomechanical Motion of Furylfulgide Crystals

Abstract: Plate-like microcrystals of a photochromic furylfulgide bend toward the light upon UV irradiation and then straighten upon visible light irradiation. The reversible bending was observed over 200 cycles of alternating irradiation with UV and visible light. The mechanism of bending could be explained by the X-ray crystallographic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 21 publications
3
88
0
Order By: Relevance
“…[33][34][35][36][37][38][39][40][41][42][43][44] First, 1 H and 13 C isotropic chemical shifts and 13 C chemical shift tensors were measured in the solidstate, and then both isotropic and tensor quantities were quantitatively compared to DFT predictions for the SSRD candidates. 13 C tensor values were measured using the TOSS-t 1 -deTOSS (sites C5/C7, C12/C14, C15, and C16) and xCSA (sites C6 and C13) experiments ( Fig. 4 shows the two-dimensional 1 H-13 C HETCOR spectrum used to partially assign the 1 H and 13 C resonances of the SSRD; the assigned chemical shifts are summarized in Table 4.…”
Section: Candidate Rankings From Nmr Crystallographymentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37][38][39][40][41][42][43][44] First, 1 H and 13 C isotropic chemical shifts and 13 C chemical shift tensors were measured in the solidstate, and then both isotropic and tensor quantities were quantitatively compared to DFT predictions for the SSRD candidates. 13 C tensor values were measured using the TOSS-t 1 -deTOSS (sites C5/C7, C12/C14, C15, and C16) and xCSA (sites C6 and C13) experiments ( Fig. 4 shows the two-dimensional 1 H-13 C HETCOR spectrum used to partially assign the 1 H and 13 C resonances of the SSRD; the assigned chemical shifts are summarized in Table 4.…”
Section: Candidate Rankings From Nmr Crystallographymentioning
confidence: 99%
“…These materials take advantage of photochemical reactions to convert photon energy directly into mechanical work. [6][7][8][9][10][11][12][13][14][15][16][17][18] In most cases, these dramatic shape changes rely on the formation of a bimorph structure, where interfacial stress between spatially distinct regions of reactant and photoproduct drives the deformation. 1 For example, the cis-trans photoisomerization of azobenzene molecules embedded in liquid crystal polymers can drive dramatic lightinduced bending and curling.…”
Section: Introductionmentioning
confidence: 99%
“…Various types of photomechanical behaviors such as contraction [8,10], expansion [11], OPEN ACCESS bending [8,[11][12][13][14][15][16][17], separation [18], twisting [19], and rolling [12] have been reported so far. Although photochromic compounds such as diarylethenes [8,19], furylfulgide [20], azobenzene [21,22], anthracene carboxylates [23][24][25][26][27][28], salicylideneaniline [29], 4-chlorocinnamic acid [30], 1,2-bis(4-pyridyl)ethylene salt [31], benzylidenedimethylimidazolinone [32], and others [33] exhibit photochemical reactions in the crystalline phase, their photomechanical motions in the crystal are almost bending. It is essential for the development of the research field of photomechanical crystals to investigate the crystal bending behavior in detail.…”
Section: Introductionmentioning
confidence: 99%
“…T he growing recognition that rapid energy transfer between molecules of tightly packed, ordered crystals of molecular solids could be utilized as a physical platform for actuation from the nanoscale to the macroscale has recently boosted research on mechanically responsive organic-based molecular crystals [1][2][3][4][5][6][7][8][9][10][11][12] . This rapidly expanding research field has revealed an increasing number of examples of oftentimes serendipitous observations of nano-, milli-and macro-sized single crystals that hop [12][13][14] , bend [15][16][17][18][19][20] , curl 21,22 , twist [23][24][25] or swim 26 when exposed to light, heat or external pressure.…”
mentioning
confidence: 99%